The War of 1812 - Cunningham, Kevin, 1966- (Expansion of our nation., 2019)
Briefly explores the history of the War of 1812, fought among the British and their Native American allies against the United States over control of the Great Lakes territory bordering Canada and over shipping and trading access on the Atlantic. Discusses the major battles and military and political leaders who changed the course of the war. Includes a glossary.